Komunikasi Informasi Motivasi dan Edukasi tentang Stunting kepada Keluarga Berisiko Stunting dan Calon Tim Pendamping - Sitti Patimah; Suchi Avnalurini Sharief; Harpiana Rahman; Nukman Nukman (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
West Sulawesi Province is the second highest  the prevalence of stunting in Indonesia. Polman Regency has the highest in West Sulawesi (36%), so prevention efforts are needed through mentoring to groups at risk of stunting and and family support officers.This community service aims toassess the effectiveness of mentoring on knowledge, attitudes and self-efficacy of families at risk of stunting and candidate for family mentoring in stunting prevention efforts. Mentoring was provided to young women, pregnant women and mothers with toddlers, and prospective family support team officers (28 people) using the communication, information, motivation and education (CIME) method regarding the problem of malnutrition and its impacts, midwifery care for at-risk groups, as well as perspectives Islam about the role of the family in creating children without stunting.Test was conducted before and after mentoring, then analyzed using the McNemar and wilcoxon test. There were 10.7% had never heard of stunting, and 89.3% of the participants knew the term stunting as a short child and experienced growth and development disorders. There was an increase of participants' knowledge scores by 2.25 points significanly (p=0.010), sufficient knowledge was 10.7% (p=0.549), positive attitudes by 3.5% (p=1,000), and high self-efficacy by 28.6% (p=0.008). It was concluded that mentoring on participants had a positive effect on improving knowledge, attitudes, and self-efficacy in stunting prevention.